2021
DOI: 10.3390/jcm10122576
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Neutrophil Gelatinase-Associated Lipocalin Is Useful for Predicting Mortality in Critically Ill Patients

Abstract: Elevated neutrophil gelatinase-associated lipocalin (NGAL) occurs in a wide range of systemic diseases. This study examined the clinical utility of plasma NGAL to predict intensive care unit (ICU) and in-hospital mortality in critically ill patients. A total of 62 patients hospitalized in a mixed ICU were included; pNGAL, creatinine, and C-reactive protein (CRP) were assayed on four consecutive days (D1-D4) following ICU admission. APACHE II score (Acute Physiology and Chronic Health Evaluation) was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…32 Although one study conducted in the mixed ICU found that CRP level measured at discharge was not a predictor of readmission or death, 29 other studies showed that CRP concentration in plasma is significantly correlated with mortality predictors in the ICU, especially in patients diagnosed with sepsis. 51,52 The predictive value (area under the curve) of CRP at admission for mortality was 0.576 in critically ill patients. 53 In this study, we found that the maximum level of CRP concentration in plasma on the 14th day of admission in the group with fiber supplement was significantly lower than that in the group without a fiber supplement, indirectly indicating that fiber supplement can reduce the inflammation status, which may be beneficial in improving mortality in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Although one study conducted in the mixed ICU found that CRP level measured at discharge was not a predictor of readmission or death, 29 other studies showed that CRP concentration in plasma is significantly correlated with mortality predictors in the ICU, especially in patients diagnosed with sepsis. 51,52 The predictive value (area under the curve) of CRP at admission for mortality was 0.576 in critically ill patients. 53 In this study, we found that the maximum level of CRP concentration in plasma on the 14th day of admission in the group with fiber supplement was significantly lower than that in the group without a fiber supplement, indirectly indicating that fiber supplement can reduce the inflammation status, which may be beneficial in improving mortality in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is an acute‐phase reactant, as a response to IL‐6, that can be detected in several types of inflammation and also in bacterial infection, and it is a measure that helps in the diagnosis of bacterial infection 32 . Although one study conducted in the mixed ICU found that CRP level measured at discharge was not a predictor of readmission or death, 29 other studies showed that CRP concentration in plasma is significantly correlated with mortality predictors in the ICU, especially in patients diagnosed with sepsis 51,52 . The predictive value (area under the curve) of CRP at admission for mortality was 0.576 in critically ill patients 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of NGAL both in urine and plasma appeared to improve as patients progressed through their ICU stay. The authors suggested that serial measurements of NGAL may be of added value in an ICU setting to predict AKI occurrence in critically ill patients [ 29 , 30 , 31 ]. Moreover, plasma NGAL levels evaluated at ICU admission predict acute kidney injury in adult patients [ 32 ], with additional accuracy when analyzed together with eGFR [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has conducted in-depth analyses of biomarkers related to SA-AKI, demonstrating that the plasma neutral gelatin associated lipocalin (pNGAL) level at discharge can predict the recovery potential of renal function in SA-AKI patients ( 20 ). A recent study showed that pNGAL can predict the risk of death of critically ill patients during hospitalization and ICU stay ( 21 ). However, for SA-AKI patients, it is unclear whether pNGAL can predict the risk of death.…”
Section: Discussionmentioning
confidence: 99%